Feral horse social stability in Tornquist park, Argentina - Scorolli, Alberto Luis (2010)
Feral horses ( Equus ferus caballus ) exhibit harem defense polygyny, and harem-bands are generally considered to be social units stable in time. We studied an unmanaged feral horse population with very high density and few predators in Tornquist Provincial Park, Argentina. Horses were observed on a fixed route 20 km long that covered the entire study area. The horses were individually identified based on coat color and characteristic marks on face and legs. Data on social group composition was taken monthly from 1995 to 1997, seasonally from 1998 to 2000, and monthly from 2000 to 2003. We calculated the percent of harem-bands formed and dissolved, the percent of adult female change and stallion tenure. Social stability was lower than previously reported, with 20% new harem-bands formed and 18% harem-bands dissolved annually. The average rate of change of adult females was 20% per year, and the stallion mean tenure of their harem- bands was four years. We found no significant relationship between social instability and population density or autumn-winter rainfall. In Tornquist Park the majority of harem-bands remained stable along each year during the eight years. However some harems were unstable, and some adult females changed harem-bands. At the same time many feral horses changed from their original harem-bands during the study period and this became evident only through long-term research.